2015
DOI: 10.1128/jvi.01232-15
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystal Structures of Antibody N60-i3 and Antibody JR4 in Complex with gp120 Define More Cluster A Epitopes Involved in Effective Antibody-Dependent Effector Function against HIV-1

Abstract: Accumulating evidence indicates a role for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
106
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(111 citation statements)
references
References 75 publications
5
106
0
Order By: Relevance
“…3), which were mainly due to on-rate effects, as evaluated by SPR. In the case of anti-cluster A antibodies, this is consistent with previous mutagenesis and structural data indicating that tryptophan 69 is localized within the cluster A epitope, contributing to the conformation of this region recognized by this family of antibodies (15,(18)(19)(20)43). However, in the case of CoRBS antibodies, these results are consistent with a model in which mutants W69G, W69A, W69I, and W69L do not spontaneously sample the CD4-bound conformation.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…3), which were mainly due to on-rate effects, as evaluated by SPR. In the case of anti-cluster A antibodies, this is consistent with previous mutagenesis and structural data indicating that tryptophan 69 is localized within the cluster A epitope, contributing to the conformation of this region recognized by this family of antibodies (15,(18)(19)(20)43). However, in the case of CoRBS antibodies, these results are consistent with a model in which mutants W69G, W69A, W69I, and W69L do not spontaneously sample the CD4-bound conformation.…”
Section: Resultssupporting
confidence: 81%
“…Since it has been previously reported that the inner domain layers modulate recognition of gp120 by CD4i antibodies (15,16,30), we next examined the binding capacity of our panel of W69 gp120 variants to CD4i antibodies recognizing the coreceptor binding site (CoRBS; 17b and 48d) and anti-cluster A antibodies, known to be potent mediators of ADCC responses (A32, N5-i5, and N60-i3) (15,19,43,45,46). It was previously shown that CD4i antibodies preferentially recognize the CD4-triggered monomeric gp120, but they are still capable of binding to unliganded gp120 with roughly 10-to 20-fold lower affinities (15,18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such conformational changes have been reported for both the outer and inner domains of gp120 (35)(36)(37). Here we have specifically analyzed the changes associated with the outer domain harboring the CD4 binding site itself.…”
Section: Resultsmentioning
confidence: 99%
“…In a desire to reveal structural elements that discriminate and delineate the essence of the CD4-induced (CD4i) conformational rearrangements in the HIV envelope, we and others have investigated gp120 structures using "conditional" probes, MAbs, that specifically define epitopes associated with CD4i transitions of gp120 (33)(34)(35)(36)(37)(38)(39)(40)(41). Here we describe the analysis of gp120 with a select panel of five well-established CD4i MAbs that target the core outer domain.…”
mentioning
confidence: 99%